2021
DOI: 10.3390/nu13072404
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status Impact on Diet Quality and Body Mass Index in Eight Latin American Countries: ELANS Study Results

Abstract: Poor health and diet quality are associated with living within a low socioeconomic status (SES). This study aimed to investigate the impact of SES on diet quality and body mass index in Latin America. Data from the “Latin American Health and Nutrition Study (ELANS)”, a multi-country, population-based study of 9218 participants, were used. Dietary intake was collected through two 24 h recalls from participants of Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru and Venezuela. Diet quality was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 54 publications
(69 reference statements)
1
24
0
5
Order By: Relevance
“…Georgina Gómez et al found that SES matches the quality and variety of food [ 26 ]. A multilevel study on childhood determinants of obesity (2019) reported family income and the amount of child allowance was related to obesity and weight gain [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Georgina Gómez et al found that SES matches the quality and variety of food [ 26 ]. A multilevel study on childhood determinants of obesity (2019) reported family income and the amount of child allowance was related to obesity and weight gain [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous ELANS findings have shown that poorer socioeconomic conditions were associated with less diet quality and diversity as well as fewer micronutrients adequacy ratios [ 43 ]. High alcohol intake is associated with less healthy dietary patterns [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have concluded that people with low socioeconomic status are more likely to choose inexpensive, high-calorie, and less nutrient-dense foods as their primary source of nutrition [ 28 , 29 ]. Conversely, people with high socioeconomic status are more connected to greater affluence and food access, leading to high dietary quality with nutrition adequacy [ 30 , 31 , 32 ].…”
Section: Literature Reviewmentioning
confidence: 99%